Cancer metastasis of an unknown primary location into a postoperative kelody scar after a mine blast wound of the neck - Kovalyov, O. O.; Zavhorodnii, S. M.; Tolok, O. P.; Kubrak, M. A.; Kovalov, K. O.; Ковальов, Олексій Олексійович; Завгородній, Сергій Миколайович; Толок, О. П.; Кубрак, Михайло Анатолійович; Ковальов, Костянтин Олексійович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of this article is analysis of a clinical case of adenocarcinoma metastases in keloid scar tissue, which occurred after gunshot wounds to the body. Clinical observation. A young man, a military serviceman, developed a keloid scar after a landmine-explosive wound and primary surgical treatment of a neck wound, in which 2 years after excision, a metastasis of intestinal-type adenocarcinoma was detected (Cytokeratin-20+, Cytokeratin-7-, CDX-2+ and SATB 2+). With the help of clinical, endoscopic and radiological methods (computed tomography and positron emission tomography / computed tomography), the primary tumor and additional metastases in the neck, chest, abdominal cavity and pelvis could not be detected. The article analyzes the possible mechanisms of the rare case of metastasis of adenocarcinoma in the tissue of an uninfected keloid scar and discusses the concept of the formation of a premetastatic niche in the early stages of carcinogenesis of a preclinical tumor. Conclusions. This observation raises new questions for fundamental and translational studies of the process of hematogenous metastasis during the parallel progression of the primary tumor and its metastases. Мета роботи – аналіз клінічного випадку метастазування аденокарциноми у тканини келоїдного рубця, що виник внаслідок вогнепальних поранень тіла. Клінічне спостереження. У молодого чоловіка, військовослужбовця, після мінно-вибухового поранення та первинної хірургічної обробки рани шиї виник келоїдний рубець. Через 2 роки після висічення у ньому виявлено метастаз аденокарциноми кишкового типу (Cytokeratin-20+, Cytokeratin-7-, CDX2+, SATB2+). За допомогою клінічних, ендоскопічних і радіологічних методів (комп’ютерна томографія та позитронно-емісійна томографія / комп’ютерна томографія) первинну пухлину та додаткові метастази у шиї, грудній, черевній порожнині та малому тазі виявити не вдалося. Проаналізовано можливі механізми рідкісного випадку метастазування аденокарциноми у тканини неінфікованого келоїдного рубця. Наведено концепцію формування преметастатичної ніші на ранніх стадіях канцерогенезу доклінічної пухлини. Висновки. Описане спостереження ставить нові питання щодо процесу гематогенного метастазування під час паралельного прогресування первинної пухлини та її метастазів.
Метастаз раку невідомої первинної локалізації в операційний келоїдний рубець після мінно-вибухового поранення шиї
Kovalyov O. O., - ORCID ID: 0000-0001-8191-3132; Zavhorodnii S. M. - ORCID ID: 0000-0003-3082-3406; Kubrak M. A. - ORCID ID: 0000-0003-4051-9336; Kovalov K. O. - ORCID ID: 0009-0009-2232-3429.
Keywords: metastasis; adenocarcinoma; scar; keloid; military trauma; метастаз; аденокарцинома; келоїдний рубець; військова травма